Geometrically synchronous watermarking algorithm based on the corner feature - LIU Quan1; ZHANG Le1; ZHANG Yong-gang2; Christian Bessiere3; FU Qi-ming1; WANG Xiao-yan1 (Tongxin xuebao)
Simple geometric attacks could destroy watermark or its position,causing the failure of most watermarking algorithm.A geometrically synchronous watermarking algorithm robust based on the corner feature was proposed.In this paper,the feature point was detected on the normalization of the image to resist geometric attack;the combination of Harris and MIC corner detected algorithm was utilized to extract steady corner based on analyzing the advantages and disadvantages of the two algorithm;the watermarking information was statistic embed in the shape of rings instead of changing the simply one pixel.Sufficient experiments demonstrate the robustness of this approach,especially in resisting geometry attack such as RST（rotation,scaling and translation）.